2022
DOI: 10.1021/acsfoodscitech.1c00398
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-QTOF-IMS-Based Metabolite Fingerprinting of Underutilized Cordia myxa Fruits and Leaves: A Nutraceutical Source

Abstract: The present investigation focused on the chemical composition and metabolomics of Cordia myxa fruits and leaves collected from five locations in Himachal Pradesh, India. Both fruits and leaves exhibited a substantial amount of phenolics in the range of 9.65−26.22 mg GAE/g and 5.35−33.28 mg GAE/g, respectively, followed by appreciable flavonoid content. Higher antioxidant activity was detected in Shahpur leaf extract (SLE) (IC 50ABTS 0.27 mg/mL) and Raja ka Talab fruit extract (RFE) (IC 50ABTS 0.21 mg/mL) among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 59 publications
(112 reference statements)
0
6
0
Order By: Relevance
“…Accordingly, the antioxidant activity of ELCM was also higher than that of C. myxa fruit extract (ELCM, 336.58 ± 19.37 mg/ml; C. myxa fruit extract, IC 50 > 6,000 mg/ml) [ 34 ]. Recently, it has been reported that rutin is contained together with p -coumaric acid or caffeic acid in the C. myxa leaves extract [ 35 ]. We further identified the presence of rutin together with rosmarinic acid in ELCM (supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the antioxidant activity of ELCM was also higher than that of C. myxa fruit extract (ELCM, 336.58 ± 19.37 mg/ml; C. myxa fruit extract, IC 50 > 6,000 mg/ml) [ 34 ]. Recently, it has been reported that rutin is contained together with p -coumaric acid or caffeic acid in the C. myxa leaves extract [ 35 ]. We further identified the presence of rutin together with rosmarinic acid in ELCM (supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of mass spectrometry were previously described by Kumar et al . (2022). Furthermore, the collective information of WJP extract in the form of .cef file were analysed with mass profiler professional (MPP) software (Agilent Technology, version B.12.00) for extensive data mining (Dadwal et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The gradient elution conditions were -A (90%) and B (10%) from 0 to 7 min; A (10%) and B (90%) from 7 to 17 min; and A (90%) and B (10%) from 17 to 24 min at a flow rate of 0.2 mL min −1 . The parameters of mass spectrometry were previously described by Kumar et al (2022). Furthermore, the collective information of WJP extract in the form of .cef file were analysed with MASS PROFILER PROFESSIONAL (MPP) software (Agilent Technology, version B.12.00) for extensive data mining (Dadwal et al, 2022).…”
Section: Uhplc-qtof-lc/ms-based Non-targeted Comprehensive Metabolomicsmentioning
confidence: 99%
“…, solution A comprising 0.1% formic acid in water and solution B comprising 0.1% formic acid in acetonitrile (ACN), was used at a flow rate of 0.30 mL/min for separation of metabolites as explained in Kumar et al and Dadwal et al. , The peaks were monitored at 280 nm, and the quantification of phenolic acids and flavonoids was performed by plotting the calibration curve for each standard at different concentrations along with their respective retention times and UV spectra as per ICH guidelines. The linearity range, regression equation with r 2 values, LOD, and LOQ of individual phenolic acids and flavonoids are presented in Table S6.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolites were separated and identified using high-resolution 6560 Ion Mobility Q-TOF LC/MS (Agilent, Santa Clara, USA). The technique uses a two-solvent system with mobile phases A (0.1% formic acid in water) and B (0.1% formic acid in acetonitrile) in a gradient elution condition, as mentioned in Kumar et al The parameters of mass spectrometry were explained earlier . Furthermore, the collective sample information was processed with MassHunter Qualitative Analysis software (version B.06.00, Agilent Technology) for extensive data mining .…”
Section: Methodsmentioning
confidence: 99%